Assessing sport and recreation programmes’ service quality at hotels and resorts: Towards enhancing customer participation - Lim, Khong Chiu; Radzuwan, Radzliyana; Cheah, Swee Ting (David Publishing, 2014)
Many issues and challenges are faced by the managers and professionals in managing sport and recreation programmes today.Although many previous researches on service quality provided by the organizations had been explored, very few studies pertaining to service quality in sport and recreation programmes in local hotels and resorts have been emphasized.This study aims to assess customers’ perceptions of service quality in sport and recreation programmes and to determine the differences between customers’ perceptions of service quality in terms of their gender and nationality.A total of 450 respondents from the hotels and resorts located in coastal areas of the northern Peninsular Malaysia participated in the survey.They were asked to respond to a series of the adapted service quality (SERVQUAL) items to measure five dimensions of service quality including tangibles, assurance, responsiveness, reliability, and empathy. Results from this study revealed that the customers’ perceptions of the overall services in sport and recreation programmes provided by the hotels and resorts were satisfactory.It was also indicated that there was no significant difference between male and female customers’ perceptions of service quality in sport and recreation programmes. Conversely, the results revealed that there was a significant difference between local and foreign customers’ perceptions of sport and recreation services provided. These findings had implications on sport and recreation programmes in relation to designing effective management and marketing strategies at hotels and resorts.